A Heuristic Approach to Media Literacy: Teaching Fake and Real News - Mishra, Pallavi (International Journal of Psychosocial Rehabilitation, 2020)
In spite of upholding as an objective, a commitment to ethical standards of journalism, a spate of claims of “fake news” appear to be a new problem in epistemology. In the fast-moving internet age, fake news spreads faster through social media platforms, gets viral and leads to tragic results. The responsibility of the fourth pillar of democracy has increased manifolds as it has diverse impressions. The present study aims to emphasize the importance of understanding the difference between fake news and misinformation, such as mistakes reported in a news story. This research paper highlights a few cases which led to turmoil in the nation due to the proliferation of fake news through social media. The article uses Netnographic analysis of the content posted on social media platforms to comprehend how Fake news influence netizens across a spectrum of online involvement. A specific set of information which was fake originated and manifested on the Internet in India were studied. The paper explores how educators can help through media literacy to identify Fake News. Findings include a variety of pathways through which Fake news is cultivated. These data have made it possible to formalize the strategies of Media Literacy. Consequently, the paper identifies how Media Literacy can develop an understanding of the sources that can be trusted.